2018
DOI: 10.3390/su10010111
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Total Factor Energy Efficiency and Its Influencing Factors on Key Energy-Intensive Industries in the Beijing-Tianjin-Hebei Region

Abstract: Abstract:In order to realize the synergistic optimization management of energy efficiency in the key energy-intensive industries of the Beijing-Tianjin-Hebei (Jing-Jin-Ji) region, this paper calculates the total factor energy efficiency (TFEE) of 27 industries in the Jing-Jin-Ji region. We discover that the manufacturing of raw chemical materials and chemical products, the smelting and processing of ferrous metals, and the production and supply of electric power and heat power are key industries, considering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Contrary to this conclusion, Choi et al concluded in the study of the Sustainable Performance of the Steel Industry in Korea, that most steel firms are increasing returns to scale, so they can enhance their efficiency by increasing their scale [4]. It is noteworthy that even if Korea and China share many common key drivers for green growth [2], the role of key drivers could differ [3,4]. Nonetheless, these two countries share a strong potential to cooperate together on sustainable development strategies such as the emission-trading scheme (ETS) in the macro-perspective, and regional green supply chain management in the micro-perspective.…”
Section: Feasibility Issues Of the Regional Cooperationmentioning
confidence: 71%
See 1 more Smart Citation
“…Contrary to this conclusion, Choi et al concluded in the study of the Sustainable Performance of the Steel Industry in Korea, that most steel firms are increasing returns to scale, so they can enhance their efficiency by increasing their scale [4]. It is noteworthy that even if Korea and China share many common key drivers for green growth [2], the role of key drivers could differ [3,4]. Nonetheless, these two countries share a strong potential to cooperate together on sustainable development strategies such as the emission-trading scheme (ETS) in the macro-perspective, and regional green supply chain management in the micro-perspective.…”
Section: Feasibility Issues Of the Regional Cooperationmentioning
confidence: 71%
“…Sustainable development is positively related to economic growth in China and Korea, but negatively related with energy efficiency improvements in Russia and the Democratic People's Republic of Korea (DPRK), while it is relatively complicated in Japan and Mongolia due to a combination of these factors [2]. More specifically, in the analysis of total factor energy efficiency (TFEE) of 27 industries in the Jing-Jin-Ji region, Li et al found the fact that the TFEE changes in the three major industries in the Jing-Jin-Ji region are caused by technological progress [3]. Contrary to this conclusion, Choi et al concluded in the study of the Sustainable Performance of the Steel Industry in Korea, that most steel firms are increasing returns to scale, so they can enhance their efficiency by increasing their scale [4].…”
Section: Feasibility Issues Of the Regional Cooperationmentioning
confidence: 99%
“…The EEE is the dependent variable and the explanatory variables used in this study are GDP per capita, carbon intensity, energy intensity, and the openness index. The explanatory variable GDP per capita is repeatedly used in previous studies [40,41]. The second variable, energy intensity affects a country's carbon dioxide emissions.…”
Section: Regression Analysismentioning
confidence: 99%
“…From the perspective of research methods, some studies used social network analysis (SNA) [27][28][29] to analyze the regional carbon emission spatial network structure. Most of the research on carbon emissions focuses on carbon emission measurement and decomposition, carbon emissions' influencing factors, and carbon emission efficiency [30][31][32]. When using traditional spatial measurement methods to analyze carbon emissions and their influencing factors, most of the literature only considers geographically similar factors.…”
Section: Literature Reviewmentioning
confidence: 99%